Graft failure in human donor corneas due to transmission of herpes simplex virus. Issue 7 (1st July 2000) - Biswas, S; Suresh, P; Bonshek, R E; Corbitt, G; Tullo, A B; Ridgway, A E A
Abstract : AIM: To report the clinical consequences of contamination of human donor corneas by herpes simplex virus (HSV) in organ culture. METHODS: Two patients without previous history of ocular HSV infection underwent penetrating keratoplasty (PK), one for keratoconus and the other for Fuchs' endothelial dystrophy. One patient suffered primary graft failure while the other developed a persistent epithelial defect, ultimately resulting in graft failure. Viral culture of swabs taken from both corneas during the early postoperative period was undertaken. The failed donor corneas were examined histopathologically by immunohistochemistry (IHC) for HSV-1 antigens, transmission electron microscopy (TEM), and by polymerase chain reaction (PCR) for HSV DNA. Both failed corneas were replaced within 6 weeks of the initial surgery. The records of the fellow donor corneas were also examined for evidence of infection. RESULTS: HSV was cultured from both corneas during the early postoperative period. Histology of both donor corneas demonstrated a thickened corneal stroma with widespread necrosis of keratocytes and loss of endothelial cells. IHC showed keratocytes positive with antibodies to HSV-1 antigens. TEM demonstrated HSV-like viral particles within degenerating keratocytes. PCR performed on the failed corneal grafts was positive for HSV-1 DNA, whereas PCR performed on the excised host corneal buttons was negative in both patients. Records of the fellow donor corneas showed that one cornea was successfully transplanted into another recipient after 18 days in organ culture, whilst the other was discarded because of extensive endothelial cell necrosis noted after 15 days in organ culture. CONCLUSION: HSV within a donor cornea may cause endothelial destruction in organ culture and both primary graft failure and ulcerative keratitis after transplantation. Endothelial necrosis of a donor cornea in culture also raises the possibility of HSV infection within the fellow cornea.